2004
DOI: 10.1051/vetres:2004041
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of classical swine fever virus on a porcine aortic endothelial cell line

Abstract: -The effect of classical swine fever (CSF) virus on some phenotypic and functional features of an established porcine aortic endothelial cell (AOC) line was investigated. AOC cells show most of the characteristics of primary endothelial cells, avoiding the alterations and senescence that these cells undergo after a few passages in culture. AOC cells were susceptible to CSF virus infection to a high degree, reaching 90% of CSF virus positive cells after 24 h of infection; however as with other porcine susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Other in vitro investigations showed that CSFV also disrupted secretion of IFN-α and proinflammatory cytokines in porcine aortic and kidney endothelial cell lines [7,11]. It is to emphasize that CSFV-infected mo-DC were able to mature only when TNF-α and IFN-α were added into culture medium [13].…”
Section: Discussionmentioning
confidence: 94%
“…Other in vitro investigations showed that CSFV also disrupted secretion of IFN-α and proinflammatory cytokines in porcine aortic and kidney endothelial cell lines [7,11]. It is to emphasize that CSFV-infected mo-DC were able to mature only when TNF-α and IFN-α were added into culture medium [13].…”
Section: Discussionmentioning
confidence: 94%
“…CSFV infection induced a functional decrease in the pro-coagulant activity of the ECs, which were highly susceptible to CSFV infection. 33 the inhibitory effects of APS on porcine viruses infection have verified 34 and APS has been observed to regulate the levels of immunomodulating compounds in many different cell types. 35,36 The manifestation of adhesion molecules, including P-selectin and E-selectin, was inhibited by APS and persisted while the ECs were stimulated with CSFV, which could promote the expression of both P-and E-selectin ( Figure 2AB).…”
Section: Discussionmentioning
confidence: 89%
“…CSFV infection induced a functional decrease in the pro-coagulant activity of the ECs, which were highly susceptible to CSFV infection (Campos et al, 2004). The inhibitory effects of APS on porcine viruses infection have verified (Xue et al, 2017) and APS has been observed to regulate the levels of immunomodulating compounds in many different cell types (Wu et al, 2017; Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%